Prarancangan Pabrik Isopropil Asetat Dari Asam Asetat Dan Isopropanol Kapasitas 28.000 Ton/Tahun - Purnama, Hendra (2017)
In the industrial development, one of promising industries in chemical engineering is isopropyl acetate. Up to date in Indonesia there is no estabilished isopropyl acetate plant, the prospect of isopropyl acetate plant is profitable on prospective. Isopropyl acetate is widely used in chemical industries such as active solvents of some synthetic resins including ethyl cellulose, cellulose acetate, cellulose butyrate, cellulose nitrate, some vinyl copolymers, polystyrene, and methacrylic resins. Other important usages of this compound are solvents for paints, coatings, printing ink solvents, ingredients in perfume/cosmetics, as well as extracting agents on the production of medicines. To fulfill the domestic needs of isopropyl acetate which are currently provided from abroad and the potential opportunity to export,the capacity of isopropyl acetate plant is designed to be 28,000 ton/year with raw material acetic acid of 2,101.2566 kg/hour and isopropanol 1,550.6921 kg/hour . The isopropyl acetate is produced by reacting acetic acid and isopropanol in reactive distillation reactor at 87.1°C and 1 atm pressure with amberlyst catalyst 15. This reaction occurs exothermically. The plant is planned to stand in Cilegon Industrial Estate, Banten in 2020 with an area of 48,732 m2. To support the process, the utility unit requires water as much as 256,871 m3/year, and electricity of 357.29 kW. From the economic analysis it is found that the respective the, return on investment (ROI) before and after taxes and 17.05% and 13.64%, pay out time (POT) before and after taxes are 3.7 years and 4.23 years, break- Even point (BEP) 55.46%, and the shut down point (SDP) 24.35%. While the discounted cash flow (DCF) is 39.3%. From economic point of view, the isopropyl acetate plant is worthy of consideration for its establishment